Hubungan Pola Asuh Orang Tua Dengan Kejadian Stunting Pada Anak Usia 24-59 Bulan Di Wilayah Puskesmas Kuta Cot Glie Kecamatan Kuta Cot Glie Kabupaten Aceh Besar Tahun 2022 - Mirta Agustina; Fauzi Ali Amin; Anwar Arbi (Journal of Health and Medical Science, 2023)
The 2022 report from the Kuta Cot Glie Community Health Center, Kuta Cot Glie District, Aceh Besar District, shows that 37.8% of children aged 24-59 months in their working area are stunted. The stunting rate among five-year-old infants (toddlers) in Aceh is ranked 31st out of 34 provinces in Indonesia with a percentage of 37.3 percent. This research shows that the stunting rate is still a public health problem in Aceh and can become a threat to future generations. This study aims to find out the relationship between parenting style and the incidence of stunting in children aged 24-59 months in the Kuta Cot Glie Health Center, Kuta Cot Glie District, Aceh Besar District in 2022. This research is descriptive analytic with cross sectional design. Data collection was carried out by interviewing using a questionnaire. The population in this study were all mothers with toddlers aged 24-59 months in the Kuta Cot Glie Health Center, Kuta Cot Glie District, Aceh Besar District, namely 82 respondents and the sample was determined using a non-probability sampling technique, namely the total sampling technique. Total sampling is a sampling technique in which all members of the population are sampled. This research was conducted in March 2022. The statistical test used was the Chi Square Test (?=95%). The results of the univariate study showed that children who experienced stunting (37.3%), exclusive breastfeeding (78.04%), MP-ASI (68.29%), nutrition campaigns (71.95%), holding classes for pregnant women ( 75.60%), deworming (90.24%), managing malnutrition (57.31%), and providing additional food (52.43%). The results of the bivariate statistical test showed that there was a relationship between exclusive breastfeeding (p = 0.000), MP-ASI (p = 0.000), nutrition campaigns (p = 0.000), holding classes for pregnant women (p = 0.000), deworming (p = 0.015) ), handling of malnutrition (p = 0.039) and providing additional food (p = 0.008), with the incidence of stunting in children aged 24-59 months in the Kuta Cot Glie Health Center, Kuta Cot Glie District, Aceh Besar District in 2022.